Association of coronary calcium score with endothelial dysfunction and arterial stiffness. (November 2020) - Torngren, Kristina; Rylance, Rebecca; Björk, Jonas; Engström, Gunnar; Frantz, Sophia; Marko-Varga, György; Melander, Olle; Nihlen, Ulf; Olsson, Henric; Planck, Maria; Wennersten, André; Malmqvist, Ulf; et al.
Abstract: Background and aims: The aim of the study was to determine potential associations between endothelial dysfunction and arterial stiffness, measured by peripheral arterial tonometry, and coronary artery calcium score (CACS) assessed by computed tomography (CT). Methods and results: The BIG3 study is a prospective longitudinal, non-interventional, pulmonary-cardiovascular cohort study exploring the three major smoking-induced diseases: cardiovascular disease, chronic obstructive pulmonary disease, and lung cancer, in a 45–75 aged cohort (mean 62 years), enriched in smokers. Computed tomography of the chest with assessment of CACS was performed in a selected subset of the participants (n = 2080). Peripheral arterial tonometry (EndoPAT) was used to assess endothelial function and arterial stiffness measured as reactive hyperaemia index (RHI) and augmentation index (AI), respectively. We observed significant associations of CACS, endothelial dysfunction, and arterial stiffness with several risk factors for coronary heart disease including age, sex, BMI, diabetes mellitus, and blood pressure. There was significant association of CACS, classified into three levels of severity, with RHI and AI ( p  = 0.0005 and p  = 0.0009, respectively). For groups of increasing CACS (0, 1–400 and > 400 Agatston score), RHI decreased from median 1.89 (1.58–2.39), and 1.93 (1.62–2.41) to 1.77 (1.51–2.10). AI increased from median 14.3 (5.7–25.2), and 16.4 (8.1–27.6) to 18.0 (9.1–29.2). RHI, but not AI, remained significantly associated with CACS after risk factors adjustment. Conclusions: In this large study of coronary artery calcium and vascular function, we found an association between CACS and both endothelial dysfunction and arterial stiffness, indicating that they may reflect similar mechanisms for development of cardiovascular disease. Graphical abstract: Image 1 Highlights: We studied associations between endothelial dysfunction and arterial stiffness, measured by peripheral arterial tonometry, and coronary artery calcium score (CACS) assessed by computed tomography (CT). We observed associations of CACS, endothelial dysfunction, and arterial stiffness with several risk factors for coronary heart disease. There was significant association of CACS with peripheral endothelial function and arterial stiffness.